Seasonal variability of metazooplankton in coastal sub-Antarctic waters (Beagle Channel) - Aguirre, Gaston Ezequiel (2012)
The aim of this study was to analyse the variability in the species composition and abundance of the metazooplankton community in different coastal areas of the Beagle Channel (southern tip of South America) during a seasonal cycle. Sampling was conducted during November (spring) 2005, March (summer), June (autumn) and September (winter) 2006 at 12 coastal stations. Copepods were the most abundant group throughout the study, and their assemblages were composed of a mixture of species typical of the south-western Atlantic, the south-eastern Pacific and the Southern Ocean. Among them, Oithona similis, Ctenocalanus citer and Drepanopus forcipatus were the dominant species. The copepod Acartia tonsa was the only taxon that displayed a spatial pattern of abundance, showing higher densities in areas with lower salinities. The community structure showed a strong temporal pattern. The metazooplankton community in March and June was mainly composed of copepods, while in November and September the community showed a greater diversity. In these two months high densities of meroplanktonic larvae were found, in coincidence with higher chlorophyll-a concentration. This temporal pattern seems to be more dependent on primary production than on physical factors such as temperature or salinity. The absence of a clear spatial pattern may suggest that the studied area of the Beagle Channel behaves as a semi-enclosed water body.